Cost-effectiveness of digoxin, pacing, and direct current cardioversion for conversion of atrial flutter in neonates. (6th March 2018) - Prasad, Deepa; Steinberg, Joni; Snyder, Christopher
Abstract: Introduction: Newborn atrial flutter can be treated by medications, pacing, or direct current cardioversion. The purpose is to compare the cost-effectiveness of digoxin, pacing, and direct current cardioversion for the treatment of atrial flutter in neonates. Materials and methods: A decision tree model was developed comparing the efficacy and cost of digoxin, pacing, and direct current cardioversion based on a meta-analysis of published studies of success rates of cardioversion of neonatal atrial flutter (age<2 months). Patients who failed initial attempt at cardioversion progressed to the next methodology until successful. Data were analysed to assess the cost-effectiveness of these methods with cost estimates obtained from 2015 Medicare reimbursement rates. Results: The cost analysis for cardioversion of atrial flutter found the most efficient method to be direct current cardioversion at a cost of 10 304, pacing was next at 11 086, and the least cost-effective was digoxin at 14 374. The majority of additional cost, regardless of method, was from additional neonatal ICU day either owing to digoxin loading or failure to covert. Direct current cardioversion remains the most cost-effective strategy by sensitivity analyses performed on pacing conversion rate and the cost of the neonatal ICU/day. Direct current cardioversion remains cost-effective until the assumed conversion rate is below 64.6%. Conclusion: The most cost-efficient method of cardioverting a neonate with atrial flutter is direct current cardioversion. It has the highest success rates based on the meta-analysis, shorter length of stay in the neonatal ICU owing to its success, and results in cost-savings ranging from 800 to 4000 when compared with alternative approaches.